Profiles of undergraduates’ fear of missing out (FoMO): Influences in academic goals and decision-making processes - Suárez-Perdomo, Arminda; Garcés-Delgado, Yaritza; Arvelo-Rosales, Carmen Nuria (Australasian Journal of Educational Technology, 2025)
The aim of the present study was to identify profiles of fear of missing out on social networks in university students and their possible influence on academic goals and decision-making processes. The participants in this study were 1838 students from 30 Spanish universities. The fear of missing out on social networking in university students scale, the academic goals questionnaire and the decision-making scale were used for data gathering. Through latent profile analysis, fear of missing out profiles were identified and differences between groups were analysed through the three-step Bolck-Croon-Hagenaars method. The results showed three profiles with respect to the fear of missing out on social networking sites: low FoMO, moderate FoMO and high FoMO. Significant differences between profiles were observed for social valuing and achievement goals, as well as for stress and dissatisfaction, vigilance, avoidance and task procrastination. Implications for practice or policy University student welfare and counselling services may offer voluntary seminars or workshops aimed at strengthening students’ academic goals and developing coping strategies in decision-making processes. Universities should consider the impact of students’ social life and the use of social networking sites when designing guidance and support actions. Higher education institutions should promote integrated institutional responses that address students’ emerging personal, professional, and social needs, considering academic, social, and personal dimensions of student development.